Left is not woke - Neiman, Susan (Polity Press, 2023)
If you're woke, you're left. If you're left, you're woke. We blur the terms, assuming that if you're one you must be the other. That, Susan Neiman argues, is a dangerous mistake. The intellectual roots and resources of wokeism conflict with ideas that have guided the left for more than 200 years: a commitment to universalism, a firm distinction between justice and power, and a belief in the possibility of progress. Without these ideas, Neiman argues, they will continue to undermine their own goals and drift, inexorably and unintentionally, towards the right. In the long run, they risk becoming what they despise. One of the world's leading philosophical voices, Neiman makes this case by tracing the malign influence of two titans of twentieth-century thought, Michel Foucault and Carl Schmitt, whose work undermined ideas of justice and progress and portrayed social life as an eternal struggle of us against them. A generation schooled with these voices in their heads, raised in a broader culture shaped by the ruthless ideas of neoliberalism and evolutionary psychology, has set about changing the world. It's time they thought again.